2017
DOI: 10.1186/s40001-017-0254-0
|View full text |Cite|
|
Sign up to set email alerts
|

Application of transiliac approach to intervertebral endoscopic discectomy in L5/S1 intervertebral disc herniation

Abstract: ObjectiveTo discuss the significance and the short-term effect of bone puncture technique in transiliac approach to intervertebral endoscopic discectomy for the treatment of L5/S1 intervertebral disc herniation.MethodsNineteen patients were diagnosed as L5/S1 disc herniation and treated using transiliac approach to endoscopic discectomy (group I), and 20 patients were diagnosed as non-L5/S1 disc herniation and underwent conventional approach (group R). Leg pain was evaluated by VAS. MacNab ratings of the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…The SAP only eliminates endoscope insertion. Several investigators reported that a high IC disturbed the transforaminal approach (TFA) in L5/S1 LDH [8,16,17]. The entry angle of TFA is generally 25°–35°, and the skin entry point is 10–13 cm from the midline.…”
Section: Discussionmentioning
confidence: 99%
“…The SAP only eliminates endoscope insertion. Several investigators reported that a high IC disturbed the transforaminal approach (TFA) in L5/S1 LDH [8,16,17]. The entry angle of TFA is generally 25°–35°, and the skin entry point is 10–13 cm from the midline.…”
Section: Discussionmentioning
confidence: 99%
“…There are several recognized percutaneous endoscopic approaches to LDHs: interlaminar, transforaminal, posterolateral, and transiliac [77,78]. As an aggregate group, endoscopic discectomy is associated with decreased operative time and less blood loss with no increase in overall complications, reoperation rates, or wound infection when compared to open discectomy [79].…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Given the difficulty in utilizing the endoscopic approach with high iliac crests, Bai et al applied a transiliac approach to endoscopic discectomy [77]. In comparison to the conventional transforaminal approach, there was no difference in 12-month outcomes, usage of fluoroscopy, or perioperative neurovascular injury.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…Interlaminar approach can escape the blockade of crista iliaca, and offer several advantages including a faster puncture orientation, a shorter operation time, and less intraoperative radiation exposure[ 18 ]. Application of transiliac approach to intervertebral endoscopic discectomy in L5/S1 LDH has also been suggested[ 19 ]. Additionally, it is reported that compared with the L5/S1 level, the L4/5 level might be easier to master after short-term professional training[ 20 ].…”
Section: Patient-related Conditionsmentioning
confidence: 99%